PKM Peningkatan Produksi Kerupuk “Kerupuk Fantasy” Melalui Rekayasa Oven Pengering Kerupuk di Kecamatan Pedurungan, Kota Semarang - Ma’mun, Hisyam; Mukhtar, Agus; Androva, Althesa; Burhanudin, Aan; Khusnun Naufal, Gostsa; Malik, Muchammad (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
The main problem in drying crackers is that drying is not uniform and still uses solar heat. In the rainy season, the process of drying crackers cannot be done quickly or takes longer, thereby reducing the amount of cracker production in cracker MSMEs. The solution to the problem in the drying process is to use technology in the form of a cracker drying oven. The cracker drying oven was made at the UMKM Kerupuk Fantasi location so you could try it straight away. From the experimental results it is known that the drying process at a temperature of 75˚C results in a greater reduction in cracker weight than the drying process at a temperature of 70˚C. The drying process in a cracker drying oven is carried out for 3 hours to get perfectly dry crackers. Drying time using a cracker drying oven is faster than drying time using solar heat. By reducing drying time, cracker production capacity will increase.